2015
DOI: 10.5056/jnm15028
|View full text |Cite
|
Sign up to set email alerts
|

The Bitter Taste Receptor Agonist Quinine Reduces Calorie Intake and Increases the Postprandial Release of Cholecystokinin in Healthy Subjects

Abstract: Background/AimsBitter taste receptors are expressed throughout the digestive tract. Data on animals have suggested these receptors are involved in the gut hormone release, but no data are available in humans. Our aim is to assess whether bitter agonists influence food intake and gut hormone release in healthy subjects. MethodsTwenty healthy volunteers were enrolled in a double-blind cross-over study. On 2 different days, each subject randomly received an acid-resistant capsule containing either placebo or 18 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
83
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(97 citation statements)
references
References 37 publications
(42 reference statements)
7
83
1
2
Order By: Relevance
“…Van Avesaat et al . reported no significant change in CCK, GLP‐1, and PYY after intraduodenal infusion of quinine, while another study did report an increase in postprandial CCK release after intradoudenal quinine administration . Ghrelin release was not altered after intragastric administration of DB in humans .…”
Section: Introductionmentioning
confidence: 94%
“…Van Avesaat et al . reported no significant change in CCK, GLP‐1, and PYY after intraduodenal infusion of quinine, while another study did report an increase in postprandial CCK release after intradoudenal quinine administration . Ghrelin release was not altered after intragastric administration of DB in humans .…”
Section: Introductionmentioning
confidence: 94%
“…In addition to the bitter masking effect, in vitro experiments carried out in our working group have shown that NaHED, the more water soluble sodium salt of HED, may also have the potential to stimulate mechanisms regulating hunger as it affected glucose uptake and serotonin release in Caco‐2 cells . Another recent study demonstrated that bolus administration of 18 mg quinine hydrochloride, a bitter taste receptor agonist, reduced ad libitum calorie intake in healthy adults, providing evidence that bitter taste receptors may be involved in the regulation of food intake. We, therefore, hypothesized that bitter‐masking agents, like HED, might exert opposite effects.…”
Section: Introductionmentioning
confidence: 98%
“…Study design 69 The current study consisted of 5 independent protocols studying the following parameters: provided 80% power to detect significant differences of 15% with an alfpha of 0.05 (13,23,92 24). Based on the results obtained from the lingual (study 1) and gastrointestinal (study 2) 93 bitter sensitivity studies it was decided to only include female participants for the last 3 study 94 protocols.…”
mentioning
confidence: 99%